Crystallisation kinetics of diopside-Ca-Tschermak based glasses nucleated with Cr2O3 and Fe2O3. (26th March 2009) - Goel, Ashutosh; Tulyaganov, Dilshat U.; Kansal, Ishu; Shaaban, Essam R.; , Jose M.F. Ferreira
We report on the crystallisation behaviour and non-isothermal crystallisation kinetic studies of two diopside (CaMgSi2O6)-Ca-Tschermak (CaAl2SiO6) based glasses nucleated with Fe2O3 and Cr2O3. The two glasses with compositions corresponding to CaMg0.75Al0.5Si1.75O6 and Ca0.9Mg0.65Li0.1Al0.5La0.1Si1.75O6 were prepared by the melt-quenching technique. Structural investigations on the glasses have been made by density measurements, molar volume and infrared spectroscopy (FTIR). Non-isothermal crystallisation kinetic studies have been employed to study the mechanism of crystallisation in all the four glasses. Bulk crystallisation was obtained and augite crystallised out being the primary crystalline phase in both the glasses. Crystallisation sequence in the glasses has been followed by X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM) and FTIR.